Take-off force in ski jumping: age and gender differences - Yamamoto, K.; Takeda. T.; Kondo, Y.; Yoshida, M.; Katayose, M. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: The main purposes of take-off phase are to raise the centre of mass and to gain a forward-rotating angular momentum (Schwameder 2008). This study focused on the former, and aimed to analyze the age and gender differences by the take-off force.